1994
DOI: 10.1021/ja00093a022
|View full text |Cite
|
Sign up to set email alerts
|

Pentakis(.eta.1-phosphinine)iron: Synthesis, Structure, and Mode of Formation

Abstract: In order to elucidate the preferred mode of coordination-( ) or ij6(«•)-we have reacted phosphinine (C5H5P) with the open ferrocene (2,4-Me2-7/5-C5Hj)2Fe. The product, pentakis(7i*-phosphinine)iron (1), was subjected to X-ray structural analysis: 1 crystallizes in the space group P2/n with the cell parameters a = 16.010

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
1
5

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 0 publications
1
61
1
5
Order By: Relevance
“…Special attention was paid to the charges of the centers of reactions: the carbon atom at position 4 and the phosphorus atom in order to establish the stronger [1], [4] dipole; this is more important in the case of polarisable dienophiles. From Table 3 we observed that the alkyl substituents decrease the energy of reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Special attention was paid to the charges of the centers of reactions: the carbon atom at position 4 and the phosphorus atom in order to establish the stronger [1], [4] dipole; this is more important in the case of polarisable dienophiles. From Table 3 we observed that the alkyl substituents decrease the energy of reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In consequence the results of PM3 calculation, except some values for ethyl derivatives, are in agreement with the experimental data and the electronic e®ects of substituents. Atomic charges listed in Table 5 emphasized that the electron withdrawing group phenyl decreases the atomic charge at C4, while electron releasing groups methyl, ethyl, isopropyl, and tert-butyl increase the atomic charge at C4, thus the [1], [4] dipole is strengthen by alkyl groups and consequently the reactions energy of these compounds are lower. The positive charge of the phosphorus atom increases in the case of phenyl substituted phosphabenzenes in position 2,4 and 6.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphinines themselves, and in some cases metal complexes thereof, have been the subjects of previous theoretical studies. [13,14] A recent example is the ab initio calculations of the homoleptic tris-(2,2'-biphosphinine) complex of tungsten with six h 1 (s) bonds. [20] Theoretical calculations have also been reported for the Pd 3 core, [21±23] but not yet for ligand-stabilized triangulo Pd 3 clusters.…”
Section: Resultsmentioning
confidence: 99%
“…[16] Phosphinines are known to have significant aromatic character; the lowest unoccupied molecular orbital (p*) of the parent compound PC 5 H 5 has a relatively high localization at phosphorus that suggests a high p-acceptor capacity. [13,14] The in-plane lone electron pair corresponds to the third highest occupied level at about À 10.0 eV, which can be compared with À 10.6 eV known for PH 3 . This implies pronounced s-donor properties.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation